Testing, referral, and treatment patterns for hepatitis C virus coinfection in a cohort of veterans with human immunodeficiency virus infection. - Fultz, Shawn L; Justice, Amy C; Butt, Adeel A; Rabeneck, Linda; Weissman, Sharon; Rodriguez-Barradas, Maria (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2003)
We examined testing, referral, and treatment of patients with hepatitis C among HIV-infected patients in the Veterans Aging 3-Site Cohort Study by using patient- and provider-completed surveys and laboratory, pharmacy, and administrative records from the Department of Veterans Affairs electronic medical record. Of 881 human immunodeficiency virus-positive patients, 43% were coinfected with hepatitis C virus. Of these, 88 (30%) reported current alcohol consumption. Only one-third were counseled to reduce or stop alcohol consumption. Coinfected patients with indications for hepatitis C treatment had a high rate of contraindications, including both medical and psychiatric comorbidities. Of the 65 patients with indications for hepatitis C therapy and free of contraindications for treatment, only 18% underwent liver biopsy and 3% received IFN. Although treatment indications are common in this population, contraindications are also common. Health care providers are often unaware of alcohol consumption that may accelerate the course of hepatitis C, increase the risk of hepatocellular carcinoma, and reduce treatment efficacy.
Keywords: Adult; Aged; Alcohol Drinking; Antiviral Agents; Carcinoma, Hepatocellular; Female; Hepacivirus; Hepatitis C; HIV; HIV Infections; Humans; Male; Middle Aged